THE IMPORTANCE OF MULCHING IN THE CULTIVATION OF MEDICINAL PLANTS (MATRICARIA CHAMOMILLA L.) AND THE EFFECTIVENESS OF MULCHING METHODS - Chulieva M. T. (Web of Journals Publishing, 2025)
This article analyzes the types of mulch materials, mulching methods, the effect of mulching on plant growth and yield, and also provides necessary information on the importance of mulching in maintaining soil moisture, controlling weeds, and stabilizing soil temperature.
Keywords: Types of mulch, mulching methods, soil fertility, organic mulch, inorganic mulch, medicinal plants.